DIAGNOSTIC HISTOPATHOLOGY OF JUVENILE GRANULOSA CELL TUMOR: HALLMARK MORPHOLOGICAL AND CYTOLOGICAL FINDINGS - Liana, Nana; Ruhsyahadati, Ruhsyahadati; Triyana, Rahma; Helmizar, Roland; Dhuha, Alief; Malik, Rifkind; Saputra, Muhammad Rizki (Yayasan Nusantara Hasana Berdikari, 2025)
Juvenile granulosa cell tumour (JGCT) is a subtype of granulosa cell tumour that predominantly affects young females, particularly those who are premenarchal, with a mean age at diagnosis of 13 years. Although rare, this tumour can occur across a wide age range, from 10 months to 67 years. Histologically, JGCT resembles the adult-type granulosa cell tumour but presents with distinct features, including aggressive growth and the absence of FOXL2 mutations. Common clinical manifestations include an abdominal mass, abdominal pain, precocious puberty in prepubertal girls due to estrogen secretion, and menorrhagia or amenorrhea in premenopausal women. Macroscopically, the tumour typically exhibits a dominant solid component, frequently accompanied by hemorrhagic and necrotic areas. High mitotic activity and variable degrees of cytological atypia are characteristic findings. The diagnosis is supported by positive immunoreactivity for inhibin, calretinin, and CD99. In early-stage disease, the primary treatment is unilateral oophorectomy with fertility preservation. In contrast, advanced stages often require total hysterectomy and adjuvant chemotherapy. Prognosis is highly dependent on disease stage; patients with stage I disease have a survival rate of up to 97%, whereas advanced-stage disease is associated with a poorer outcome. This review aims to provide a comprehensive overview of the epidemiology, pathogenesis, clinical manifestations, diagnostic approaches, and management strategies of Juvenile Granulosa Cell Tumour (JGCT). It also underscores the importance of early detection and the development of more effective therapeutic options to enhance clinical outcomes.